SELECTIVE SEPARATION OF CALCIUM AND MAGNESIUM SALTS FROM DOLOMITE AND MODELING AND OPTIMIZATION OF PRECIPITATES FORMED WITH BICARBONATE IONS IN AQUEOUS MEDIA. - Karshiyeva Madina Mitin kizi, Kholiyorova Sabina Farkhod kizi; Khusanov Eldor Safariddinovich (Research Focus International Scientific Journal, 2025)
This research investigates the selective separation of calcium and magnesium ions from dolomite using aqueous extraction and precipitation techniques. The study focuses on the reactions of Ca²⁺ and Mg²⁺ with bicarbonate ions (NaHCO₃ and (NH₄)₂HCO₃), leading to the formation of carbonate-based precipitates. Experimental conditions such as temperature, pH, and ionic strength are analyzed to optimize the process. Mathematical modeling is applied to simulate the behavior of the system in aqueous media. The findings contribute to enhancing the efficiency of mineral processing, softening of hard water, and environmentally friendly methods for utilizing dolomite resources.